The Impact of Business Intelligence and Knowledge Management on Sustainability Performance in the Tourism Industry in Algeria - Brahami Menaouer; Sabri Mohammed; Matta Nada (Indonesian Journal of Sustainability Accounting and Management, 2022)
In today’s business context of globalization, competition, knowledge economy, rapid technological changes, and external environmental factors, knowledge management and business intelligence on the tourism level have received increased attention in an effort to identify smart performance factors and change the structure of organizations. Similarly, the tourism industry has experienced considerable development during recent decades. Moreover, sustainability is becoming increasingly important for society and is especially critical in the operation of the tourism industry. It is well known that sustainability is a prerequisite to carrying out any activity. This evaluates the relationship between knowledge management in operations and business intelligence systems on the sustainability performance within the tourism industry in Algeria. A total of 126 questionnaires were distributed to the study sample. A multiple regression analysis was used to test the hypotheses of the study. This study concludes that there is a positive relationship between knowledge management processes and sustainability performance. Further, the components of business intelligence have positive impacts on sustainability performance. The results can facilitate utilizing the knowledge management processes and business intelligence implementation in Algeria’s tourist industry.